Perancangan UI Dan UX Aplikasi Pemesanan Buket Menggunakan Metode Double Diamond - Perdana, Dimas Elang; Totohendarto, Moch Hafid; Maâ€™ruf Nugroho, Imam (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Business development in Indonesia has been growing, especially the type of bouquet business, one of which is the Desshine Bouquet Store. However, currently Desshine Store does not have any specific activities or strategies that handle marketing and ordering products made. Looking at the problem of Deshhine Store which still uses social media and is not mobile-based. Therefore, a user interface design is needed before designing the application. Certain techniques are needed to design a bouquet ordering user interface that can facilitate the delivery of information and the ordering process for users. This study presents the design of the user interface of the bouquet ordering application using the Double Diamond method and user experience testing using the User Experience Questionnaire (UEQ) method which aims to measure the results of the design of the user interface design. The test results found that three UEQ scales were rated very good "Excellent", namely on the scale of attractiveness, efficiency, and dependability. While three UEQ scales are in the good rating of "Good", namely the perspicuity, stimulation and novelty scales.Keyword: User Interface; User Experience; Double Diamond; User Experience QuestionnaireÂ AbstrakPerkembangan usaha di Indonesia sudah semakin berkembang terlebih jenis usaha buket salah satunya Toko Buket Desshine. Namun, saat ini Toko Desshine tidak memiliki aktivitas atau strategi khusus yang menangani pemasaran dan pemesanan produk yang dilakukan. Melihat pada permasalahan Toko Deshhine yang masih menggunakan sosial media dan belum berbasis mobile, oleh karena itu diperlukan suatu desain user interface sebelum merancang aplikasi. Diperlukan suatu teknik tertentu untuk mendesain user interface pemesanan buket yang dapat memudahkan penyampaian informasi dan proses pemesanan untuk pengguna. Pada penelitian ini menyajikan perancangan user interface aplikasi pemesanan buket menggunakan metode Double Diamond dan pengujian user experience menggunakan metode User Experience Questionnaire (UEQ) yang bertujuan untuk mengukur hasil dari perancangan desain user interface. Hasil pengujian didapatkan hasil bahwa tiga skala UEQ berada pada penilaian sangat bagus â€œExcellentâ€ yaitu pada skala attractiveness, efficiency, dan dependability. Sedangkan tiga skala UEQ berada pada penilaian bagus â€œGoodâ€ yaitu skala perspicuity, stimulation dan novelty.Â